Radvilų dvaro istorijų aruodai - Zigmantaitė, Marta (Journal of Architecture and Urbanism, 2012)
Book “Radvilų dvaro istorijų aruodai” review. Journal of Architecture and Urbanism, 36(3), pp. 244-245.